Occurrence of hemorrhagic events related to invasive devices manipulated by nursing in anticoagulated patients - Flavia Giron Camerini; Lolita Dopico da Silva; Danielle de Mendonça Henrique; Karla Biancha Silva Andrade; Luana Ferreira de Almeida (Rev Rene)
Objective: to verify the occurrence of hemorrhagic events related to invasive devices manipulated by nursing in anticoagulated patients. Methods: retrospective cohort study, with analysis of medical records. A total of 867 medical records were investigated, from which a sample of 79 patients who received continuous infusion of sodium heparin was selected. The types of hemorrhagic events and the different invasive devices were submitted to non-parametric statistical treatments and to the association tests. Results: the most common types of hemorrhagic events occurred in the skin (47.4%); puncture site (15.8%); airways (15.8%); genitourinary system (15.8%) and gastrointestinal system (10.5%). Patients with nasoenteral catheters had a 15.8-foldhigher risk of gastrointestinal bleeding (p=0.032). Conclusion: the rate of bleeding events (21.5%) was high, and more frequent in the skin. Patients with nasoenteral catheters have a higher risk of gastrointestinal bleeding and patients with indwelling bladder catheters have a seven-fold increased risk of hematuria.